Anti‐inflammatories and mucociliary clearance therapies in the age of CFTR modulators. (12th November 2019) - Perrem, Lucy; Ratjen, Felix
Abstract: Cystic fibrosis (CF) is a genetic and life‐limiting disease caused by mutations in the CF transmembrane conductance regulator (CFTR) gene. This multi‐system disease is characterized by progressive lung disease and pancreatic insufficiency amongst other manifestations. CFTR primarily functions as a chloride channel that transports ions across the apical membrane of epithelial cells but has other functions, including bicarbonate secretion and inhibition of sodium transport. Defective CFTR disrupts these functions, causing viscous and dehydrated mucus to accumulate, compromising the airway lumen and contributing to obstructive pulmonary disease. The combination of CFTR dysfunction, mucus obstruction, and infection drive an exaggerated and dysfunctional inflammatory response, which contributes to irreversible airway destruction and fibrosis. CFTR modulators, an exciting new class of drugs, increase the expression and/or function of CFTR variant protein and improve multiple clinical endpoints, such as lung function, pulmonary exacerbation rates, and nutritional status. However, these genotype‐specific drugs are not universally available, the clinical response is variable, and lung function still declines over time when bronchiectasis is established. Consequently, even in the age of CFTR modulators, we must target other important aspects of the CF airway disease, such as inflammation and mucociliary clearance. This review highlights the mechanisms of inflammation and mucus accumulation in the CF lung and discusses anti‐inflammatory and mucociliary clearance agents that are currently in development focusing on compounds for which clinical trial data have recently become available.